2014
DOI: 10.3324/haematol.2014.113472
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic influence of macrophages in patients with diffuse large B-cell lymphoma: a correlative study from a Nordic phase II trial

Abstract: impact in DLBCL. [14][15][16][17] Of the macrophages, classically activated M1 type TAM have been described as "good", acting to prevent the growth of tumor tissue, whereas the alternative M2 type TAM may have an opposite effect promoting angiogenesis and tumor development. [18][19][20] Importantly, however, studies in follicular lymphoma have demonstrated that the prognostic significance of the tumor microenvironment and especially macrophages is highly dependent on a given therapy. [21][22][23] In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 47 publications
5
63
1
1
Order By: Relevance
“…6 The cohorts under study include patients with gene expression data from a Nordic phase II trial (dose-dense chemoimmunotherapy with central nervous system prophylaxis, n=38), 7 from the Cancer Genome Characterization Initiative (R-CHOP, n=92) and from the LLMPP (R-CHOP, n=233 and CHOP, n=181). Immunohistochemistry data were generated using the KP1 anti-human CD68 antibody and positive cells were counted manually.…”
mentioning
confidence: 99%
“…6 The cohorts under study include patients with gene expression data from a Nordic phase II trial (dose-dense chemoimmunotherapy with central nervous system prophylaxis, n=38), 7 from the Cancer Genome Characterization Initiative (R-CHOP, n=92) and from the LLMPP (R-CHOP, n=233 and CHOP, n=181). Immunohistochemistry data were generated using the KP1 anti-human CD68 antibody and positive cells were counted manually.…”
mentioning
confidence: 99%
“…2,17,18 Riihijarvi et al found that both CD68 mRNA levels and CD68 + tumorassociated macrophages, detected by immunohistochemistry, were adverse prognostic factors for overall survival among patients treated uniformly with chemotherapy in a prospective clinical trial. 19 In contrast, among patients treated with chemo-immunotherapy, the impact of CD68 + tumor-associated macrophages was reversed, such that patients with high CD68 + tumor-associated macrophages had improved overall survival. This interesting observation led the authors to speculate that rituximab may alter the function of tumor-associated macrophages from having a pro-survival effect to an anti-tumor one.…”
Section: Diffuse Large B-cell Lymphomamentioning
confidence: 99%
“…Recent studies demonstrated the important function of TAMs in the progression of cancers 15, 16, 17, 30. Hans et al.…”
Section: Survival‐related Genes Were Selected For Testingmentioning
confidence: 99%
“…It is demonstrated that macrophages possess anti‐tumor or tumor‐promotion effects, depending on their acquired immune‐phenotype (M1 or M2) which express different levels of chemokines, cytokines. TAMs (M2 phenotype) predict poor outcome in DBLCL patients‐treated with chemotherapy 15, 16, 17. Polymorphisms of host cytokines and immunity‐related genes were reported to play very important roles in predicting survival of DLBCL patients 7.…”
Section: Introductionmentioning
confidence: 99%